Schelling, Cavell, and the Truth of Skepticism - G. Anthony Bruno (MULPress, 2021)
This paper argues that (1) McDowell wrongly assumes that “terror”, Cavell’s reaction to the radical contingency of our shared modes of knowing or our “attunement”, expresses a skepticism that is antinomically bound to an equally unacceptable dogmatism because (2) Cavell rather regards terror as a mood that reveals the “truth of skepticism”, namely, that there is no conclusive evidence for necessary attunement on pain of a category error, and that (3) a precedent for McDowell’s misunderstanding is Hegel’s argument for necessary attunement in a system of knowing, whose refutation Schelling holds it is the “merit of skepticism” to provide.